2018
DOI: 10.1002/qj.3252
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of afternoon and evening sea‐breeze fronts on local turbulence, and on CO2 and radon‐222 transport

Abstract: We investigated sharp disruptions of local turbulence and scalar transport due to the arrival of sea-breeze fronts (SBFs). To this end, we employed a comprehensive 10-year observational database from the Cabauw Experimental Site for Atmospheric Research (CESAR, the Netherlands). Sea-breeze (SB) days were selected using a five-filter algorithm, which accounts for large-scale conditions and a clear mesoscale-frontal signal associated with the land-sea contrast. Among those days (102 in all, 8.3%), based on the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…The algorithm consists of four different filters, which are shown in Table 2. The first three are coincident with the algorithm defined in Arrillaga et al (2018), just modifying the precipitation-amount threshold for Filter 3: 0.5 instead of 0.1 mm/day, since weak and scattered showers (< 0.5 mm) do not alter the onset and development of katabatic winds. From detailed individual analysis we found that the large-scale conditions favourable for the formation of katabatic flows are those that apply for sea breezes, i.e.…”
Section: Method: Katabatic-detection Criteriamentioning
confidence: 91%
See 2 more Smart Citations
“…The algorithm consists of four different filters, which are shown in Table 2. The first three are coincident with the algorithm defined in Arrillaga et al (2018), just modifying the precipitation-amount threshold for Filter 3: 0.5 instead of 0.1 mm/day, since weak and scattered showers (< 0.5 mm) do not alter the onset and development of katabatic winds. From detailed individual analysis we found that the large-scale conditions favourable for the formation of katabatic flows are those that apply for sea breezes, i.e.…”
Section: Method: Katabatic-detection Criteriamentioning
confidence: 91%
“…The research strategy from Arrillaga et al (2018), in which they applied an objective and systematic algorithm to the observational data in order to select sea-breeze events, is followed. In this work, we adjust the algorithm for selecting events that fulfil predefined katabatic criteria.…”
Section: Method: Katabatic-detection Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, given the importance of the SB‐turbulence interaction during the AET, as was proved in Arrillaga et al (), the coincident SB events have been classified into different ABL regimes. These, are defined according to the local turbulence at the moment of the onset.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Similarly, the presence of the North Sea and the IJsselmeer (the large freshwater lake in the north of the country) have a significant impact on local weather conditions, through such effects as sea‐breeze circulation, which can alter aerosol concentration (Arrillaga et al . ) and local temperatures, as well as the modulation of diurnal and seasonal temperature cycles through the increased heat capacity of the water. At the same time, the North Sea also brings with it a thermal memory in the form of the Gulf Stream circulation, making the coastal waters warmer than they would otherwise be without the transatlantic transport of heat from the tropical and Equatorial regions (Palter, ).…”
Section: Introductionmentioning
confidence: 99%